Pneumonia in solid organ transplant recipients: a prospective multicenter study. Issue 2 (5th March 2014) - Giannella, M.; Muñoz, P.; Alarcón, J.M.; Mularoni, A.; Grossi, P.; Bouza, E.; ,
Abstract Background Pneumonia frequently affects solid organ transplant (SOT) recipients, with high morbidity and mortality. However, the few studies on pneumonia in this population are mainly retrospective, single‐center, and long‐term studies, or include patients with only one type of SOT or a specific etiology. We performed a point prevalence study to investigate epidemiology, diagnosis, therapy, and outcome of pneumonia in an unselected SOT population. Methods Italian and Spanish transplant centers were invited to report on all SOT recipients with pneumonia treated during 2 separate weeks (1 each in February and June 2012). Results In total, 35 centers (18 in Italy, 17 in Spain) agreed to participate and collected 54 cases. The incidence of pneumonia was 10.1 episodes/1000 recipients/year. Pneumonia was classified as late (>6 months) in 70.4% of cases. Pneumonia was also classified as community‐acquired (CAP), healthcare‐associated (HCAP), and hospital‐acquired (HAP) pneumonia in 40.7%, 38.9%, and 20.4% of cases, respectively. An attempt to microbiological diagnosis (≥1 sample) was made in 94.4% of patients, with a diagnostic yield of 60.7%. Causative agents included bacteria (87.1%), virus (29%), and fungi (6.4%). A multidrug‐resistant bacterium was isolated in 18.2%, 40%, and 100% of patients with CAP, HCAP, and HAP (P = 0.007), respectively. Overall, 11.1% of patients were admitted to the intensive care unit, 3.7% developed graft rejection, and graft function deteriorated in 18.5%. In‐hospital mortality was 1.9%. Conclusion Pneumonia remains a frequent problem in SOT recipients, although it occurs later in patients who are in better physical health. Therefore, harmful pathogens and worse outcome are less common than previously thought.